Prognostic Association Between Perioperative Red Blood Cell Transfusion and Postoperative Cardiac Surgery Outcomes - Li, Yanxiu; Cheang, Iokfai; Zhang, Zhongwen; Zuo, Xiangrong; Cao, Quan; Li, Jinghang (Frontiers in Cardiovascular Medicine, 2021)
Objective: To investigate the correlation between red blood cell transfusion and clinical outcome in patients after cardiac surgery. Methods: Demographic, clinical characteristics, treatment with/without transfusion, and outcomes of patients after cardiac surgery from MIMIC-III database were collected. Patients were divided into two groups according to perioperative transfusion. A multivariable logistic regression analysis was utilized to adjust the effect of red blood cell transfusion on outcomes for baseline and covariates, and to determine its association with outcomes. Results: In total 6,752 patients who underwent cardiac surgery were enrolled for the analysis. Among, 2760 (40.9%) patients received perioperative transfusion. Compared to patients without RBC transfusion, transfused patients demonstrated worse outcomes in in-hospital mortality, 1-year mortality, and all-cause mortality. Adjusting odds ratios for the significant characteristic, patients with perioperative transfusion remained significantly associated with an increased risk of in-hospital mortality (OR=2.8, 95% CI 1.5-5.1, P=0.001), 1-year mortality (OR=2.0, 95% CI 1.4-2.7, P<0.001) and long-term mortality (OR=2.2, 95% CI 1.8-2.8, P<0.001). Conclusion: Perioperative RBC transfusion is associated with a worse prognosis of cardiac surgery patients. Optimal perioperative management and restricted transfusion strategy might be considered in selected patients.